ECO SPLASH-TANK, PENYIRAM PUPUK CAIR DENGAN SUMBER SOLAR CELL SEBAGAI SOLUSI PEMUPUKAN TANAMAN MELON - Ismanto, Andi; Wicakssana, Bayu; Kurniawan, Hendi Okta; Wiranata, Muhammad Fendi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
The process of exhausting long melon cultivation is one of the rarity factor farmers grow the The long and exhausting process in melon cultivation is one of factor the farmer rarity to grow up the fruit. The liquid fertilization is done once per 2/3 days. And the spraying can reach up to 23 time until the harvesting. Not maximum liquid fertilization will take longer time and more draining. Thats way, it needs a technology which can solve both these problems in one tool. This tool is called eco splash tank. This tank can also used in remote area without electricity because it is equipped by solar panels for energy source. the one wheel using for design makes the eco splash tank has capacity 30 L and strong. The result for a single full charge can be turned on and pump for 8 hrs. and the charging time for solar panels to accu until full is 9,5 hrs. in a pilot watering can be done up to 30 plants/minute and spray up to 27 plants/minute. It increases from 20 plants/minute(watering) and 17 plants/minute (spraying). In addition the functional benefits are felt by farmers. Because they donât need to hold, pump, and by the fuel. furthermore the design of eco splash tank will be developped for agricultural crops and then RAMP Technopreneurship, patent, and a list of 107 Innovation.Key Words: Aplikator, Sprayer, Hortikulture, Solar Energy